A three-long noncoding RNA signature as a diagnostic biomarker for differentiating between triple-negative and non-triple-negative breast cancers. Issue 9 (March 2017) - Liu, Man; Xing, Lu-Qi; Liu, Yi-Jing
Abstract: Background: Triple-negative breast cancer (TNBC) is an aggressive cancer with unfavorable outcome and it is useful to explore noninvasive biomarkers for its early diagnosis. Here, we identified differentially expressed long noncoding RNAs (lncRNAs) in blood samples of patients with TNBC to assess their diagnostic value. Methods: Differential expression of lncRNAs in plasma of patients with TNBC (n = 25) and non-TNBC (NTNBC; n = 35) and in healthy controls was compared by microarray analysis and validated by real-time PCR. lncRNA expression between plasma and BC tissues was compared using Pearson correlation test. Logit model was used to obtain a new lncRNA-based score. Receiver operating characteristic analysis was performed to assess the diagnostic value of the selected lncRNAs. Results: Microarray data showed that 41 lncRNAs were aberrantly expressed. Among these, antisense noncoding RNA in the INK4 locus ( ANRIL ), hypoxia inducible factor 1alpha antisense RNA-2 ( HIF1A-AS2 ), and urothelial carcinoma-associated 1 ( UCA1 ) were markedly upregulated in plasma of patients with TNBC compared with patients with NTNBC ( P < 0.01). HIF1A-AS2 expression was positively associated with its tissue levels ( r = 0.670, P < 0.01). AUC (95% CI) of ANRIL, HIF1A-AS2, and UCA1 was 0.785 (0.660–0.881), 0.739 (0.610–0.844), and 0.817 (0.696–0.905), respectively. TNBCSigLnc-3, a new score obtained using the logit model, showed excellent diagnostic performance, with AUC of 0.934 (0.839–0.982), sensitivity of 76.0%, and specificity of 97.1%. Conclusion: ANRIL, HIF1A-AS2, and UCA1 expression was significantly increased in plasma of patients with TNBC, suggesting their use as TNBC-specific diagnostic biomarkers.